Face and shoulder massage as the element of logopedic therapy in people after tounge cancer - Hamerlińska, Agnieszka; Gniezdzia – Buc, Izabela (Journal of Education, Health and Sport, 2017)
This article concerns the use of facial and shoulder massage in speech therapy. Contains synthetic characteristics of the causes, methods and consequences of the treatment of tongue cancer. The concept of classical massage has been described, the factors determining proper massage performance and its technique have been described. It has been justified to use massage therapy in people after removing the tongue.